2015
DOI: 10.1128/iai.00291-15
|View full text |Cite
|
Sign up to set email alerts
|

Tir Triggers Expression of CXCL1 in Enterocytes and Neutrophil Recruitment during Citrobacter rodentium Infection

Abstract: The hallmarks of enteropathogenic Escherichia coli (EPEC) infection are formation of attaching and effacing (A/E) lesions on mucosal surfaces and actin-rich pedestals on cultured cells, both of which are dependent on the type III secretion system effector Tir. Following translocation into cultured cells and clustering by intimin, Tir Y474 is phosphorylated, leading to recruitment of Nck, activation of N-WASP, and actin polymerization via the Arp2/3 complex. A secondary, weak, actin polymerization pathway is tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
(68 reference statements)
1
16
0
Order By: Relevance
“…IECs isolated from uninfected mice were used as a control (five mice per group). Examination of IECs by microscopy and flow cytometry revealed that IEC preparations were enriched by over 90% ( Crepin et al., 2015 ). Immunofluorescence microscopy revealed that IECs extracted from uninfected mice exhibited typical columnar shape and projection of actin-rich BB microvilli.…”
Section: Resultsmentioning
confidence: 99%
“…IECs isolated from uninfected mice were used as a control (five mice per group). Examination of IECs by microscopy and flow cytometry revealed that IEC preparations were enriched by over 90% ( Crepin et al., 2015 ). Immunofluorescence microscopy revealed that IECs extracted from uninfected mice exhibited typical columnar shape and projection of actin-rich BB microvilli.…”
Section: Resultsmentioning
confidence: 99%
“…Such successful predictions also serve to validate the model. The success of the current study opens the prospect of using a similar approach to analyze the influence of other effectors on the immune response, such as Tir, which can affect the recruitment of neutrophils (31). …”
Section: Discussionmentioning
confidence: 99%
“…Cells were stained for surface markers (such as CD4 + CD8 − T cells, B220 + CD3 − B cells, and CD11b + Ly6G + neutrophils) in PBS containing 1% bovine serum albumin with 0.5% sodium azide (PBA) for 30 min at 4°C and fixed with IC fixation buffer (eBioscience) as described previously (31). Nonviable cells were excluded using a fixable near-infrared dead cell staining kit with excitation at 633 or 635 nm (L10119; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we compared the proteomes of IECs purified from mice infected with WT, Δ espO and Δ espO -p espO at 8 DPI. Assessing purity by flow cytometry revealed that the IEC preparations were enriched by over 90% [ 26 ]. For the proteomic analysis, we only considered changes to protein abundance between WT and Δ espO if they were fully restored upon Δ espO complementation.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, bone marrow transplantation from WT mice into Myd88-/- mice restored CCH [ 6 ]. In addition, the T3SS effector Tir, in a process dependent on Y451 and Y471, has been shown to modulate secretion of Cxcl-1 and recruitment of neutrophils 14 DPI [ 26 ]. Importantly, while exhibiting a similar level of shedding, mice infected with C .…”
Section: Discussionmentioning
confidence: 99%